2014
DOI: 10.3892/mmr.2014.2167
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate inhibits growth of human chronic myeloid leukemia K562 cells via reactive oxygen species generation and caspases

Abstract: Abstract. Phenethyl isothiocyanate (PEITC), a potential cancer chemopreventive constituent of cruciferous vegetables, including watercress, has been reported to inhibit cancer cell growth by arresting the cell cycle and inducing apoptosis in various human cancer cell models. However, the role of PEITC in the inhibition of human chronic myeloid leukemia (CML) K562 cell growth and its underlying mechanisms have yet to be elucidated. In the present study, PEITC was found to induce cell death through the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The apoptotic cell death in these cell lines was reversed by the ROS scavenger, NAC. A number of studies are consistent with our results, ROS mediated cell death in many types of cancer cells ( 37 , 45 , 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…The apoptotic cell death in these cell lines was reversed by the ROS scavenger, NAC. A number of studies are consistent with our results, ROS mediated cell death in many types of cancer cells ( 37 , 45 , 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…The regulation of HO-1 is under the control of signaling components (Shirley and Micheau, 2010;Rushworth et al, 2011) and many transcription factors, including nuclear factor-(erythroid-derived 2)-like 2-related factor 2, activating transcription factor 4 (ATF4), and activator protein-1 (He et al, 2001;Yu et al, 2014). Additionally, its expression is closely related to the endoplasmic reticulum apoptotic pathway mediated by caspases and the CCAAT-enhancer-binding protein homologous protein (CHOP) pathway (Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that isothiocyanates exhibit antitumor activity, inhibiting growth and metastasis in various human cancer cell models. Other studies have revealed that phenethyl isothiocyanate (PEITC) suppresses the growth of cancer cells in vitro and in vivo (6). Several cellular responses to this potential chemopreventative agent have been previously described, including apoptosis mediated by c-Jun amino terminal kinase and extracellular signal-regulated kinase (7,8).…”
Section: Introductionmentioning
confidence: 99%